Assessing and treating sexual dysfunctions in Orthodox Jewish couples: a summary of 41 consecutive cases. Issue 9 (21st October 2019) - Friedman, Steven
ABSTRACT: Orthodox Jews are a distinct subgroup with specific beliefs and values towards sexuality, reproduction, modesty, and openness to mental health treatment. This paper reviews the treatment of 41 Orthodox Jewish couples who presented for sex therapy. Most couples were referred by a rabbinical leader. The most common presenting problem was an unconsummated relationship; present in 27 couples. In 34 couples the initial presenting complaint was a male sexual problem yet in 20 of 41 couples both partners described having some sexual problem. Almost 50 per cent of both men and women were also diagnosed with a comorbid psychiatric disorder, which was almost always previously undiagnosed. The most common presenting problems were vaginismus, male inhibited arousal, and/or inhibited male orgasm. Two case examples illustrate some adaptations to assessment and treatment that can be helpful in treating sexual problems in Orthodox Jewish couples.